PTU-137 Enhanced Diagnostic Performance of Symptom-Based Criteria for Irritable Bowel Syndrome by History and Diagnostic Evaluation. (17th August 2016) - Sood, R; Camilleri, M; Gracie, DJ; Gold, MJ; To, N; Law, GR; Ford, AC
Abstract : Introduction: Symptom-based criteria to diagnose irritable bowel syndrome (IBS) positively perform only modestly. Our aim was to assess whether including other items from the clinical history and diagnostic workup improves their performance. Methods: We collected complete symptom, colonoscopy, and histology data from 318 consecutive, unselected adult patients with lower gastrointestinal (GI) symptoms in secondary care. The reference standard used to define presence of true IBS was patient-reported lower abdominal pain or discomfort associated with a change in bowel habit, in the absence of organic GI disease. Sensitivity, specificity, and positive and negative likelihood ratios (LRs), with 95% confidence intervals, were calculated for Rome III criteria, as well as for modifications, incorporating nocturnal symptoms, results of simple blood tests (haemoglobin (Hb) and C-reactive protein (CRP)), measures of somatisation, and/or affect (hospital anxiety or depression scale (HADS) score). Results: Sensitivity and specificity of Rome III criteria for identifying IBS was 69.6%, and 82.0% respectively, with positive and negative LRs of 3.87 and 0.37. Clinically useful enhancements in positive LRs when combining Rome III criteria with items from the clinical history, and blood tests, are shown in the table. Conclusion: Incorporating nocturnal symptoms, somatisation, and affect from the clinical history, and haemoglobin and CRP measurements, enhances performance of symptom-based criteria for IBS. Our findings suggest a different approach to the development of future diagnostic criteria should be used. Disclosure of Interest: None Declared